The Effect Of Trust And Convenience On Customer Satisfaction With Purchasing Decisions As An Intervening Variable Purchase Decision As An Intervening Variable E-Commerce On Shopee In Medan City - Sucitra, Sucitra (Al-Adzkiya Publisher, 2024)
The purpose of this research is to test and analyze the influence of Trust and Convenience on consumer satisfaction with purchasing decisions as an intervening variable for E-Commerce at Shopee in Medan City directly and indirectly. The approach used in this research is an associative approach. The population in this research is all E-Commerce consumers at Shopee in Medan City whose number is unknown. The sample in this study used the lameshow sampling technique, totaling 100 E-Commerce consumers at Shopee in Medan City, Medan. The data analysis technique used is path analysis using SEM-PLS. The results of this research show that Trust has a significant effect on Consumer Satisfaction through Purchasing Decisions as an intervening variable because it has a P Value of 0.010, so 0.010 < 0.05, thus it can be stated , and Convenience has a significant effect on Consumer Satisfaction through Purchasing Decisions as an intervening variable because it has a P Value of 0.006 so 0.006 < 0.05.